Growth effect of income inequality in sub-Saharan Africa: Exploring the transmission channels - Ibrahim Abidemi Odusanya; Anthony Enisan Akinlo (International Journal of Management and Economics, 2020)
Sub-Saharan Africa (SSA) ranks as the second most unequal region globally (in terms of income distribution), harboring 10 of the 19 most unequal countries in the world. This paper explores the channels through which income inequality exerts its effects on economic growth in SSA. The study spans the period 1995-2015, focusing on 31 SSA countries. Findings from the two-step system generalized method of moments suggest that income inequality exerts a significant positive effect on economic growth via the saving transmission channel, while it has a statistically significant negative effect on economic growth in the region through the channels of fertility, credit market imperfection, and fiscal policy.
Keywords: C23; C33; D31; F43; N47; 650; income inequality; growth; transmission; channels; Africa